(untitled) (Global Journal of Medical Research, 2014)
The application of implants for dental and orthopedic surgery has increased rapidly within the past few decades. In craniomaxillofacial surgery, different implant systems have been applied, for example, for dental and bone replacement or osteosynthesis plates and screws. These implants may be made of pure titanium or a titanium alloy, usually titanium-aluminumvanadium (Ti-6Al-4V). The surface can he turned or Machined or a coating may cover the metal base. The reason for treating the implant surface is to obtain maximum bone-implant contact and bone-implant stability and to shorten the healing time for earlier loading. The crucial aspect of pure titanium implants is the development of titanium oxide on the surface. This oxide and other known coatings for implant material do not have high wear resistance.